OPTIMIZATION OF INTERNATIONAL LOGISTICS FLOWS BASED ON METHODS OF THE THEORY OF DECISION-MAKING IN CONDITIONS OF UNCERTAINTY - Kuzmenko, A. I.; Cherchata, A. A.; Khalipova, N. V.; Lesnikova, I. Yu. (Systems and Technologies, 2025)
The article examines the theoretical and practical aspects of optimizing international logistics flows in conditions of uncertainty in the external environment. The main factors affecting the efficiency of logistics systems on an international scale are identified, including geopolitical instability, exchange rate fluctuations, changes in customs legislation, lack of transport resources and information opacity. Special attention is paid to the application of decision-making theory methods that allow you to reasonably choose the optimal options for actions under conditions of limited or incomplete information. The paper analyzes the possibilities of using the Laplace, Wald, Savage, and Hurwitz criteria to assess the risks and effectiveness of logistics solutions. It is demonstrated how each of these criteria reflects a different level of risk attitude (from pessimistic to optimistic) and can be applied to select a delivery route, supplier, carrier or transportation scheme. The practical task of optimizing international logistics flows in the Dresden-Uzhgorod direction by road, as one of the relevant logistics corridors between the European Union and Ukraine, has been solved. For this purpose, a network graph was developed, corresponding calculations were performed and comparative diagrams were constructed.A generalized risk matrix has been developed, which allows to assess the impact of external factors on the stability of international supplies and to determine the priority directions of management actions. The results of the study confirm that the integration of decision-making methods into the international logistics management process increases its adaptability, helps reduce risks and ensures a balance between costs, time and reliability of supplies. The proposed approach can be used by exporting enterprises, transport and forwarding companies and logistics operators for strategic planning and increasing competitiveness in the world market.